KEDUDUKAN BAYYINAH, SYAHADAH DAN QARINAH DALAM PENGGUBALAN UNDANGUNDANG KETERANGAN ISLAM DI MALAYSIA - Md Noor, Ruzman (Jurnal Syariah, 2019)
This article tries to analyze the methodology of promulgation of the Islamic Law of Evidence in Malaysia. It focuses on the principles of bayyinah, syahadah and qarinah. Since the structure of the law originates from the Evidence Act 1950, which is mainly based on the principles of evidence in English common law, several modifications and insertions have to be performed through the methodology of Islamic Jurisprudence or Usul al-Fiqh. Various suggestions have been put forward in this article to ensure that the position of bayyinah, syahadah and qarinah are correctly placed in the respective law.